Cognitions That Support Concussion Reporting in Collegiate Athletes: An Analysis of a Worksheet Activity. (June 2022) - Kneavel, Meredith; Ernst, William
Background: Sports related concussions continue to be a public health concern and improving reporting behavior a focus of educational programs. While educational programs have addressed changes in knowledge of concussion symptoms, it has been challenging to design educational programs which have lasting effects on reporting behavior. Aims: The current analysis describes an intervention in which thoughts about reporting behavior are actively written down in a worksheet exercise to "pre-arm" athletes with cognitions designed to enhance reporting behavior prior to the injury event. Method: A total of 503 male and female college athletes participating in collision (football, field hockey, ice hockey, lacrosse, and soccer) and contact sports (baseball, basketball, and softball) from 7 colleges/universities competing across all three NCAA divisions provided data collected during a randomized trial of a peer concussion education program. Results: Qualitative analysis revealed 10 themes that would improve reporting including short-term benefits, faster recover, safe and healthy return to play, reporting helps the team, reporting protects the brain, risk aversion, long-term benefits, coach will be supportive, teammates will be supportive and understanding, and academic performance will be affected. Discussion: Athletes had awareness of key risks involved in concussions and understood both short- and long-term consequences. Conclusion: These findings have important implications for understanding how to change athletes' thoughts about reporting concussions.